2005
DOI: 10.1007/s00535-005-1587-y
|View full text |Cite
|
Sign up to set email alerts
|

Where is the primary site of action of CCK for initiating sphincter of Oddi relaxation?

Abstract: The delivery of bile into the duodenum is controlled by the motor activity of the gallbladder and sphincter of Oddi (SO). 1 In humans and dogs, the SO acts as a resistor to the outflow of bile. During the interdigestive period, when there is no duodenal activity, the basal pressure and rhythmic contractions of the SO exceed the hepatic secretory pressure of bile, which results in the gradual filling of the gallbladder. Ingestion of a meal induces gallbladder contraction and relaxation of the SO via the release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Importantly, the authors propose that the paradoxical response to CCK observed in patients with SO dysfunction is not mediated by CCK receptors on the smooth muscle but instead may be mediated by a mechanism requiring duodenal myoneural continuity. However, the site of action of CCK for initiating SO relaxation is still debated [18]. In contrast to the previously described study, Naruse [18] hypothesizes, on the basis of numerous surgical models, that CCK probably induces SO relaxation via activation of extrinsic nerves.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 89%
See 1 more Smart Citation
“…Importantly, the authors propose that the paradoxical response to CCK observed in patients with SO dysfunction is not mediated by CCK receptors on the smooth muscle but instead may be mediated by a mechanism requiring duodenal myoneural continuity. However, the site of action of CCK for initiating SO relaxation is still debated [18]. In contrast to the previously described study, Naruse [18] hypothesizes, on the basis of numerous surgical models, that CCK probably induces SO relaxation via activation of extrinsic nerves.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 89%
“…However, the site of action of CCK for initiating SO relaxation is still debated [18]. In contrast to the previously described study, Naruse [18] hypothesizes, on the basis of numerous surgical models, that CCK probably induces SO relaxation via activation of extrinsic nerves. He suggests that further studies should consider a broader range of CCK concentrations, along with the role of ICC, neural connections among the SO, gallbladder/common bile duct, and stomach, and whether CCK-A receptors are located on vagal afferent nerve fibers in the duodenum.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 89%
“…It indicates that acupuncture at CO11 can partially block the inhibitory effect of atropine on SO EMG. Though the exact pathway for this effect remains unclear, it may be partially attributed to the secretion of cholecystokinin (CCK) as an important ghrelin that has an excitatory effect on the SO EMG 27 .…”
Section: Discussionmentioning
confidence: 99%